Integração entre Sistemas de Informação em Saúde: o caso do e-SUS Atenção Básica - Coelho Neto, Giliate Cardoso [UNIFESP] (2019)
Introduction: In Brazil, health professionals and public managers coexist with dozens of Health Information Systems in their work environments. Some are called National Health Information System because they are used by thousands of health services to collect and send data to large databases centralized in the Ministry of Health of Brazil. Most were created in a fragmented way and disconnected from a global view of the MS software ecosystem, causing them to be born with little or no integration with each other. Some public policies have been implemented to reduce the fragmentation of National Health Information System in the Brazilian Unified Health System (SUS), among which the e-SUS AB Strategy, carried out by the Primary Health Care Department of the Ministry of Health. Objective: To describe and analyze the situation of the integration of e-SUS AB with others National Health Information Systems of Brazilian Primary Health Care. Methodology: A case study with data analysis and cross-checking of multiple sources of evidence was carried out: official publications and technical documents of MS, interviews with key informants, literature review and answers obtained through the Access to Information Law. Results and Discussion: We found 31 National Health Information Systems in production in Primary Care. It was verified that the e-SUS AB Strategy accomplished complete unification of user interfaces with 11 of these systems, incomplete integration with other 4 systems and no integration with 16 systems. Interface integration was observed in 100% of the Primary Health Care Department own systems, but no complete integration was observed with any systems of the Ministry of Health Surveillance Department. Frequency and intensity of systems use in health services appeared as less important factors, since systems with a marked use at the local level had incipient integration with e-SUS AB. Conclusion: The e-SUS AB Strategy took on the challenge of producing more integration through unified interfaces guided by the "single window" concept. The difficulties in achieving this integration are related to the historic fragmentation of Ministry of Health management, the maintenance of the (false) dichotomy between Surveillance and Health Assistance, the low governance of the e-SUS AB management area and the fragile IT governance of the MS. Decentralized IT hubs play a central role in the development of National Health Information System, but are largely ignored in the master plans and technology management committees.